1957
DOI: 10.1139/y57-056
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Adrenocorticotrophic Hormone in the Pituitary Gland

Abstract: The highly vascular, anteromedial zone of hog and beef pituitary glands, which is rich in basophilic cells, contains a concentration of ACTH from 4 to 13 times that found in the rest of the adenohypophysis. The concentration of ACTH can be correlated (r = 0.96) with the relative proportion of basophilic cells, supporting the view that the pituitary basophiles are the source of ACTH. The distribution of both basophiles and ACTH in the rat adenohypophysis is more uniform than in hog or beef glands. The posterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1960
1960
1977
1977

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Pituitary glands were removed as rapidly as possible from decapitated female animals by the technique of Rochefort & Saffran (1957). The excised pituitaries were weighed immediately and transferred to tubes containing (per pituitary) 0-5 ml.…”
Section: Methodsmentioning
confidence: 99%
“…Pituitary glands were removed as rapidly as possible from decapitated female animals by the technique of Rochefort & Saffran (1957). The excised pituitaries were weighed immediately and transferred to tubes containing (per pituitary) 0-5 ml.…”
Section: Methodsmentioning
confidence: 99%
“…F ortier [1951] introduced the hypothesis that stressors could be divided into 2 groups -neurotropic and systemic -and that the adrenal cortical response to neurotropic stressors (noise, immobilization, novel environment) required the integrity of the hypothalamic-hypophysial system. This then generated a long series of studies [Mialhe-Voloss, 1952, 1953, 1955Rochefort and Saffran, 1957;Rochefort et al, 1959;Smelik, 1960;de Wied, 1961;Smelik et a!., 1962] attempting to assess the possible role of 'posterior lobe' ACTH in the adrenal cortical response to neurotropic stressors. When it was reported that all of the 'posterior lobe' ACTH, as assessed by immunological techniques [Phifer and Spicer, 1970] and by bioassay [Kraicer et al, 1973], is contained exlusively within the PI, a re-evaluation of previously reported studies became necessary.…”
Section: Discussionmentioning
confidence: 99%